2022
DOI: 10.1002/joa3.12794
|View full text |Cite
|
Sign up to set email alerts
|

Catheter ablation in patients with atrial fibrillation and heart failure with preserved ejection fraction: A systematic review and meta‐analysis

Abstract: Background Catheter ablation for atrial fibrillation (AF) is a proven alternative to pharmacologic rhythm control in patients with heart failure with reduced ejection fraction (HFrEF). Whether outcomes differ in patients with heart failure with preserved ejection fraction (HFpEF) is of interest. Methods Medline, Scopus, and Cochrane Central Register of Controlled Trials were systematically searched to identify relevant studies. Primary efficacy outcomes of interest include atrial arrythmia recurrence and repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
(125 reference statements)
0
10
0
Order By: Relevance
“…A meta-analysis on catheter ablation in patients with HFpEF that included 7 studies and 764 patients showed the ablation to be safe and effective and associated with lower hospitalizations and the mortality rate. 15…”
Section: Management Of Patients With Hfmentioning
confidence: 99%
“…A meta-analysis on catheter ablation in patients with HFpEF that included 7 studies and 764 patients showed the ablation to be safe and effective and associated with lower hospitalizations and the mortality rate. 15…”
Section: Management Of Patients With Hfmentioning
confidence: 99%
“…Siddiqui et al 30 performed a meta‐analysis of seven observational non‐randomized studies comprising 2554 patients with HFpEF who underwent CA for AF. When comparing patients with HFpEF versus those without HF, there was no significant difference in atrial arrhythmia recurrence (RR: 1.39, 95% CI: 0.91–2.13) and stroke (RR: 0.47, 95% CI: 0.03–6.54).…”
Section: Studies Of Ca Of Af In Patients With Hfmref and Hfpefmentioning
confidence: 99%
“…When comparing patients with HFpEF versus those without HF, there was no significant difference in atrial arrhythmia recurrence (RR: 1.39, 95% CI: 0.91–2.13) and stroke (RR: 0.47, 95% CI: 0.03–6.54). Similarly, when comparing patients with HFpEF versus HFrEF, there was no significant difference in atrial arrhythmia recurrence (RR: 1.12, 95% CI: 0.92–1.37), repeat ablation (RR: 1.19, 95% CI: 0.74–1.93), all‐cause mortality (RR: 0.87, 95% CI: 0.67–1.13), all‐cause hospitalizations (RR: 1.10, 95% CI: 0.94–1.30), and cardiovascular hospitalizations (RR: 0.83, 95% CI: 0.69–1.01) 30 …”
Section: Studies Of Ca Of Af In Patients With Hfmref and Hfpefmentioning
confidence: 99%
See 2 more Smart Citations